ARTICLE SUR LE SYSTEME DE SECURITE ET D’OPTIMISATION D’UN RESEAU AU SEIN D’UNE ENTREPRISE. CAS DU RESEAU DE L’UNIVERSITE DE LUKANGA «UNILUK» - SAMSON, KAMBALE SENGEMOJA (IJRDO -Journal of Computer Science Engineering, 2021)
Communication networks play a role increasingly important in our daily activities, disruption of services they provide, or even a significant deterioration of their quality, are becoming less and less acceptable. Network security, quality control and service optimization services have become major issues that require real methodological advances in several areas. This work has analyzed the problems of optimizing the management of network bandwidth Adventist University Lukanga. For this, we treated a topic "distribution system customized bandwidth network UNILUK." Our contributions here can be divided into two components: first make a distribution system tailor bandwidth to customers and also to filter the few sites that do not agree with the philosophy of Adventist University Lukanga. To be able to execute this project, we used the pfSense technology and modeling software (Sybase power design).